Building Reputation: Proxy Wars and Transnational Identities - Marion Mercier; Arthur Silve; Benjamin Tremblay-Auger (Institute of Labor Economics (IZA), 2023)
In the context of a global security framework that mitigates interstate conflicts, nation-states establish a reputation for resolve by supporting foreign insurrections. Our theoretical predictions indicate that states with a greater number of co-ethnic groups abroad are more inclined to endorse foreign uprisings, resulting in higher political inclusion for such groups. With a dataset comprising over 280,000 ethnic group sponsor state target state year observations, our analysis corroborates the role of reputation-building through co-ethnicity narratives as a determinant of sponsor state engagement. We argue that this mechanism engenders political concessions within target states, ultimately benefiting groups associated with reputed potential sponsors.
Keywords: D74; F51; N40; P48; 330; reputation; proxy war